Videogrammetry technique for arm positioning of bio-production robot - Razali, Mohd. Hudzari; Wan Ismail, Wan Ishak; Ismail, Napsiah; Sulaiman, Md. Nasir; Shariff, Rashid (2005)
This paper describes the development of the “robot eye” system for agriculture arm robot that can predict the actual distance of the object target. Stereo pair of Videogrammetry technique and triangulation was used to determine the distance measurement of object target. By a “click” on the image of displayed developed graphical user interface created by Visual Basic V6, the three-dimensional target distance will be generated and robot arm able to move and grab the selected target automatically. The development of mathematical model for robot arm was based on Denavit-Hertenberg kinematics solutions that used to develop joint relationship of robot arm for producing the robot movement with real time simulation. Two digital cameras used and fixed at parallel stage for applying the Videogrammetry concept of coordinate detection. The user will trigger the computer for sending the signal to pneumatic solenoid valves of robot through controller card and produce proper output to locate robot arm. This project is suitable to apply on wireless agriculture robot for real application on plantation crop that is the one of the solution to apply the non-contact measurement system and potential to avoid the sunlight variation problem as stated on last.